2022
DOI: 10.3389/fnagi.2022.904085
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Clinical-Based Signature to Predict the 90-Day Functional Outcome for Spontaneous Intracerebral Hemorrhage

Abstract: We aimed to develop and validate an objective and easy-to-use model for identifying patients with spontaneous intracerebral hemorrhage (ICH) who have a poor 90-day prognosis. This three-center retrospective study included a large cohort of 1,122 patients with ICH who presented within 6 h of symptom onset [training cohort, n = 835; internal validation cohort, n = 201; external validation cohort (center 2 and 3), n = 86]. We collected the patients’ baseline clinical, radiological, and laboratory data as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The comparative analysis of clinical data derived from patients exhibiting good and poor outcomes has unveiled a noteworthy dissimilarity in terms of age distribution between the two cohorts. Aging stands as a widely acknowledged and pivotal risk determinant linked to a less favorable prognosis among individuals afflicted with SAH, as substantiated by previous studies [ 24 , 25 ]. This discovery holds noteworthy implications for clinical practice.…”
Section: Discussionmentioning
confidence: 73%
“…The comparative analysis of clinical data derived from patients exhibiting good and poor outcomes has unveiled a noteworthy dissimilarity in terms of age distribution between the two cohorts. Aging stands as a widely acknowledged and pivotal risk determinant linked to a less favorable prognosis among individuals afflicted with SAH, as substantiated by previous studies [ 24 , 25 ]. This discovery holds noteworthy implications for clinical practice.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, among the 28 eligible studies, 15 studies were multi-centered ( 27 29 , 39 , 45 , 47 , 52 , 55 , 58 64 ); five studies extracted their original data from databases ( 24 , 25 , 32 , 37 , 57 ); and the remaining 24 studies were single-centered. Most eligible studies focused on IS and 7 studies ( 23 , 32 , 39 , 40 , 48 , 60 , 63 ) on HS. A study ( 32 ) used the same four models to predict the motor function in patients with IS and HS respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Due to distinct purposes, these included studies defined poor motor function in a different manner. Specifically, it was defined as Modified Rankin Scale >1 in 4 studies ( 26 , 31 , 45 , 58 ), Modified Rankin Scale >3 in 4 ( 39 , 53 , 60 , 63 ) studies, Modified Rankin Scale >4 in two ( 25 , 42 ) studies, and Modified Rankin Scale >2 in other 34 studies. In this study, a total of 13 primary studies using radiomics as predictive factors were identified ( 27 , 30 , 36 , 37 , 49 , 51 , 52 , 54 57 , 61 , 62 ), from which 33 prediction models were extracted.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of bleeding after a cerebral hemorrhage is an important indicator of its severity. Hematoma size has been reported to be closely related to prognosis in patients with SICH (19)(20)(21). In these patients, intracranial hematoma is involved in secondary brain injury as well as mechanical injury.…”
Section: Discussionmentioning
confidence: 99%